Compare between result of analysis of variance after and before use analysis covariance to Split-blocks design - خلف كمال علوان; احمد احمد شهاب; كامل سيماء فراس (Journal of Economics and Administrative Sciences, 2018)
This research aims to study the important of the effect of analysis of covariance manner for one of important of design for multifactor experiments, which called split-blocks experiments design (SBED) to deal the problem of extended measurements for a covariate variable or independent variable (X) with data of response variable or dependent variable Y in agricultural experiments that contribute to mislead the result when analyze data of Y only. Although analysis of covariance with discussed in experiments with common deign, but it is not found information that it is discussed with split-Blocks experiments design (SBED) to get rid of the impact a covariance variable. As part application actual field experiment conducted, begun at 15/11/2015 for wheat crop in the rice research station (in the city Al-mishkhab) affiliated to the department of agricultural research/ ministry of agriculture with split-Blocks design with factors, plating dates (3 dates for wheat kind Iba 99) and seeding rates (4rates), the weight of the crop was considered Y and the variable X is the Wight of 1000 grains. As was the use of Matlab program for make analysis of variance for data of the variable Y only and for make analysis of covariance to exclude the impact of the variable X. it has been reached that the result of analysis of covariance according to data of this experiments which conducted with split-blocks design is the most accurate compared with analysis of variance.